Answer:
8 (1 - 2 y)
Explanation:
Simplify the following:
-2 x - 4 + 2 (-3 y + x) - 2 (5 y - 6)
2 (-3 y + x) = -6 y + 2 x:
-2 x - 4 + -6 y + 2 x - 2 (5 y - 6)
-2 (5 y - 6) = 12 - 10 y:
-2 x - 4 + 2 x - 6 y + 12 - 10 y
Grouping like terms, -6 y - 10 y + 2 x - 2 x - 4 + 12 = (-6 y - 10 y) + (-2 x + 2 x) + (-4 + 12):
(-6 y - 10 y) + (-2 x + 2 x) + (-4 + 12)
-6 y - 10 y = -16 y:
-16 y + (12 - 4) + (2 x - 2 x)
12 - 4 = 8:
-16 y + 8 + (2 x - 2 x)
2 x - 2 x = 0:
8 - 16 y
Factor 8 out of 8 - 16 y:
Answer: 8 (1 - 2 y)